The 2011 Forestry Commission Fiasco: Political Roots, Cultural Ramifications - Sylvie Nail (Revue Française de Civilisation Britannique)
In January 2011, the projected privatisation of the lands managed by the Forestry Commission in England led to several weeks of protests, as a result of which the coalition government backed down. This episode points to the ambivalent perceptions of the function of forests in 21st century England: adjustment tools for the Government, but also irreplaceable places fulfilling social needs. Within these, the cultural services occupy a growing place and the arts constitute essential components of multipurpose forestry, more often than not in relation to public policies concerning health, education, environment, etc. It is this unsung aspect of today’s forestry that this article will explore, so as to understand how and why the arts are summoned in wooded spaces, the cultural dimensions of forests and what English people would lose out to a privatisation that they made clear they were hostile to anyway.